ChemInform Abstract: Challenges and Opportunities in Correlating Bimetallic Model Surfaces and Supported Catalysts. Issue 7 (18th February 2014) - Porosoff, Marc D.; Yu, Weiting; Chen, Jingguang G.
Abstract Review: 49 refs.